PREVALENCE OF THE METABOLIC SYNDROME AND ITS COMPONENT ABNORMALITIES AMONG SCHOOL AGE PAKISTANI CHILDREN - Iqbal, Amina Zehra; Basharat, Sarah; Basharat, Adeel; Basharat, Shifa (Journal of Ayub Medical College Abbottabad, 2014)
Background: Concurrence of central adiposity, hypertension, hyperglycaemia, and atherogenic dyslipidaemia has been termed as the metabolic syndrome. High prevalence of the syndrome has been reported globally over the last decade. Methods: This cross-sectional study is based on a sample of eighty five children, ranging in age from six to twelve years. After parental consent, height, weight, waist circumference, and blood pressure were measured and investigation requests for fasting plasma glucose and fasting lipid profile were given. Children with known metabolic disorders, and those using metabolic-profile-altering medication were excluded. Results: The prevalence of metabolic syndrome, according to the various definitions, varied from as high as 16.5% (95% CI: 9.3-26.1%) to as low as 1.8% (95% CI: 0.03-6.4%). The most prevalent of the component abnormalities was blood pressure above 90th percentile, positive in 54% (95% CI: 43.0-65.0). HDL-c was low (‰¤1.3 mmol/L) in 36.5% (95% I: 26.3-47.6%), and waist circumference high (>75th percentile) in 30.6% (95% CI: 21.0-41.5%). Both systolic blood pressure and triglycerides to HDL-cholesterol ratio showed a linear trend of increasing with increasing quartiles of waist and body mass index (BMI). Conclusion: Depending on the cut-off values used for defining the component abnormalities, the metabolic syndrome may be quite prevalent in this population. Waist circumference above 75th percentile and even a single reading of blood pressure above 90th percentile should be considered a warning sign, indicating further investigation and lifestyle interventions. Keywords: Metabolic Syndrome, cardio-metabolic risk, central obesity, waist circumference, dyslipidaemia